Level of knowledge of hypertension among teachers of a public educational institution, Lima provinces, 2021 - Apaza Arzapalo, Diego Rolando (2023)
Objective: To determine the level of knowledge of hypertension (HTN) among teachers of IEP No. 20799 Daniel AlcidesCarrión located in Chancayllo, Chancay-Huaral, Local Education Management Unit (UGEL) No. 10, 2021. Materials and methods: A descriptive and cross-sectional study which included the entire population of teachers of IEP No. 20799 Daniel Alcides Carrión, totaling n = 60. The teachers who did not provide the informed consent were excluded, leaving a sample of n = 54. A previously validated questionnaire was used to analyze teachers’ age, sex, education level, grade level taught, place of residence, diagnosis of HTN, family history of HTN and level of knowledge of HTN. A databasewas created in Microsoft Excel and analyzed using descriptive statistics in IBM SPSS Statistics, thus determining thefrequency, proportion and mean.Results: The teachers' average age was 42.78 ± 8.44 and the largest age group consisted of adults aged 31 to 59 years, with 94 % (n = 51). Out of all individuals, 96 % (n = 52) had a high level of knowledge of HTN, as well as of the three evaluateddimensions. Women accounted for the highest percentage in the sample, with 74.10 % (n = 40). Concerning their education level, 66 % (n = 36) had a degree and, according to their grade level taught, their percentage distribution was similar inpreschool, primary and secondary schools. As for the history of HTN, 53.70 % (n = 29) had a personal or family history of thecondition and 14.80 % (n = 8) had a diagnosis of HTN. Conclusions: Teachers of IEP No. 20799 mainly had a high level of knowledge of HTN during the year 2021 and no difference was found with respect to the teachers' level of knowledge that was related or not to the history of HTN.